Three-phase three-level inverter with reduced number of switches for stand-alone PV systems - Sefa, Ibrahim; Komurcugil, Hasan; Demírbaş, Şevki; Altın, Necmi N.; Ozdemir, Saban S. (Institute of Electrical and Electronics Engineers Inc., 2017)
In this study, a three-phase four switch inverter topology is proposed for PV systems. In power stage, a three-level neutral point clamped inverter is adopted. Thus, advantageous of the multilevel inverter topologies have been obtained with reduced number of switches. The proportional-resonant controller is designed to control the output voltage of the inverter to maintain a sinusoidal output voltage with lower total harmonic distortion and less variation even for various type of loads. MATLAB/Simulink simulations results show that, both proposed three-phase three-level neutral point clamped four-switch inverter and proportional resonant controller provides fast response and sinusoidal output voltage with lower total harmonic distortion with reduced number of switch. ©2017 IEEE.
6th IEEE International Conference on Renewable Energy Research and Applications, ICRERA 2017 -- 2017-11-05 through 2017-11-08 -- San Diego -- 133700
Keywords: Four-switch inverter; NPC inverter; PR control; PV systems